Kajian Penggunaan Biourine Sapi dan Ekstrak Bawang Merah Terhadap Sifat Agronomi Tanaman Kubis (Brasicca oleracea L.) Dataran Rendah - Tutik Nugrahini; Asiah Wati; Dwi Indriani (Universitas Widya Gama Mahakam, 2018)
Cabbage (Brasicca oleracea L.) is one type of vegetable plant from the Brassicaceae family. This plant is a source of nutrients that contain nutrients, vitamins, minerals and fiber for the human body. And has economic value. Cabbage cultivation is influenced by the types of cultivated varieties that are in accordance with growing conditions. In general, cabbage plants grow on highlands. Along with advances in plant breeding technology, cabbage plants are available that can adapt to the lowlands and technically attempt to increase production by fertilizing. The study aimed to determine the effect of beef biourine, red onion extract and beef biourine and red onion extract on the agronomic properties of cabbage plants. The study was conducted for 4 months, from February to June 2018. The location of the study was carried out in the Sempaja Timur Village, Samarinda City, East Kalimantan Province. cabbage seeds, top soil, manure, husks, NPK fertilizer, cow urine, empon-empon, soybeans, brown sugar, shallots. The design used in this study is Factorial Randomized Block Design (RBD) with 2 treatments. The first treatment was beef biourine (S) with 4 levels, namely with 3 replications: s0: control (water), s1: 25% concentration of cow biourine, s2: 75% concentration of bovine biourine, s3: 100% concentration of bovine biourine and second treatment red onion extract (B) with 4 levels, namely: b0: control (water), b1: 25% concentration of red onion extract, b2: 75% concentration of red onion extract, b3: 100% concentration of shallot extract. The results of research on bovine biourine influenced plant height, number of leaves at ages 7, 14, 21, 28.35 and 42 days after planting. The weight of the crop with the best results at the level of b2 (75% biourine cow) weighing 596.58 grams, onion extract affects plant height, number of leaves at 7, 14, 21, 28.35 and 42 hst, crop weight with the best results at the m2 level (75% red onion extract) with a weight of 567.14 grams and the interaction of the treatment of beef biourine and shallots affects plant height, number of leaves at the ages of 7, 14, 21, 28.35 and 42 days and days formed at the level b2m2 (75% beef biourine and 75 red onion extracts).